Hypomagnesaemia Posing as Hypoparathyroidism (Journal of Enam Medical College, 2015)
Persistent hypocalcaemia usually is a presentation of hypoparathyroidism. When it is coupled with low parathormone levels the diagnosis seems almost certain. However, the fact that hypomagnesaemia can give rise to both hypocalcaemia and low parathormone levels gives us points to ponder. This case depicts a young woman soon after childbirth presenting with carpopedal spasm and biochemical abnormalities. Subsequent correction of hypomagnesaemia readjusts calcium, potassium and parathormone levels.J Enam Med Col 2015; 5(3): 179-181